d^2u/dx^2 - d^2u/dy^2 = 2(e^(-x)) + 3sin2y
"\\frac{d^2u}{dx^2} - \\frac{d^2u}{dy^2} = 2e^{-x} + 3\\sin 2y"
This is an inhomogeneous linear PDE. Its general solution can be obtained as a sum of a partial solution and the general solution of the corresponding homogeneous linear PDE.
Consider the homogeneous linear PDE:
"\\frac{d^2u}{dx^2} - \\frac{d^2u}{dy^2} = 0"
This is a well-known wave equation, it has the general solution "u_{hom}= f_1(x+y) + f_2(x-y)" , where "f_1" and "f_2" are arbitrary functions.
Let's find a partial solution of the form "u_p=g(x)+h(y)" , where "g" , "h" are unknown functions.
"\\frac{d^2u_p}{dx^2} - \\frac{d^2u_p}{dy^2} =g''(x)-h''(y)=2e^{-x} + 3\\sin 2y"
Hence
"g''(x)=2e^{-x}" and "g(x)=2e^{-x}" (partial solution)
"-h''(y)=3\\sin 2y" and "h(y)=\\frac{3}{4}\\sin 2y" (partial solution)
Therefore, the general solution to the given equation is
"u=u_p+u_{hom}=2e^{-x}+\\frac{3}{4}\\sin 2y+f_1(x+y)+f_2(x-y)"
Comments
Leave a comment